Process Intensification for greenhouse gas separation from biogas: More efficient process schemes based on membrane-integrated systems. (April 2015) - Brunetti, Adele; Sun, Yu; Caravella, Alessio; Drioli, Enrico; Barbieri, Giuseppe
Graphical abstract: Highlights: Biogas separation by multistage membrane system is investigated. Four operation schemes with two membrane types are analysed. Performance maps identify the most effective working conditions for each stage. Process metrics are used as complementary support for data analysis. Abstract: The separation of biogas leads to not only recovery and sequestration of CO2, but also to much greater purification and recovery of value-added CH4 able to be used, for example, to directly feed pipelines for domestic or small plants. In this work, an alternative approach for a preliminary design of separation process based on the use of polymeric membranes is proposed. Two different types of polymeric membranes were taken into account, Hyflon AD60 and Matrimid 5218, the first showing a higher permeability with respect to other membranes but a quite low selectivity (12.9), the second exhibiting a higher selectivity with respect to other membranes (41 and 100) even though a lower permeability. Four possible operation schemes using two different types of membranes in multistage configuration system are analysed as functions of the main design parameters, i.e., pressure ratio and permeation number. The achieved results are compared with certain targets and are also discussed in terms of process metrics, according to the Process Intensification Strategy. This latter analysis, coupled with a conventional one, provides an alternative point of view over the evaluation of the plant performance taking into account not only the final characteristics of the streams but also process efficiency, exploitation of raw material and energy, and the footprint occupied by the installation.